The development payoffs of good governance emerging results of a social experiment in Bulacan and Davao del Norte - Capuno, Joseph J.; Garcia, Ma. Melody S.; Sardalla, Janette S.; Villamil, Lorna G. (2002)
This study presents some corroborative evidence based on the first year of the pilot test of the Governance for Local Development (GOFORDEV) Index in twelve cities and municipalities located in the provinces of Bulacan and Davao del Norte in the Philippines. Developed in support of the country's fiscal decentralization program, the GOFORDEV Index is both a measure of good governance and a scheme to empower local groups to push for local development. Local groups - local government units, business and associations, nongovernment organizations (NGOs) and academic institutions - were mobilized as partners tasked to generate and disseminate the localities' scores in the Index. To document the possible development payoffs, process documentation studies were undertaken to identify the modifications in budget allocations and processes that may be due the Index and two rounds of household surveys were conducted to assess the constituencies' satisfaction with the delivery of basic public services and the performance of local officials and the extent of their participation in local affairs. The study also indicates that GOFORDEV Index already yielded development payoffs, even only while it gestates.
Keywords: Budget allocations and processes; Development Needs Index (DNI); Development Orientation Index (DOI); Good governance indicators; Governance for Local Development Index -- Bulacan; Governance for Local Development Index -- Davao del Norte; Human Development Index (HDI); Local development -- Philippines; Local governance; Nongovernmental organizations; Participatory Development Index (PDI); People's participation